Faktor yang Berhubungan dengan Pemilihan Alat Kontrasepsi IUD pada Pasangan Usia Subur di Puskesmas Banjarejo Kota Madiun - Reky Galih Perwira; Riska Ratnawati; Zaenal Abidin (Jurnal Surya Medika (JSM), 2022)
Intra-Uterine Device (IUD) is one of the effective contraceptives to prevent or delay pregnancy, besides being effective, the IUD has other advantages, namely having a long period of use. The purpose of this study was to analyze the factors associated with the selection of IUD contraception in couples of reproductive age. In this research, the researcher uses descriptive quantitative research as an approach. The research method uses is an analytical survey while the type of research is cross-sectional. They are 90 population as respondents with the number of samples as 73 respondents. The results of the chi-square test showed that there was a significant relationship between independent variables, namely knowledge (p-value = 0.019), acceptance of family planning information (p-value = 0.027), and husband's support (p-value = 0.010) with the choice of IUD contraception in couples of reproductive age. The researcher concludes that there is a relationship between knowledge, acceptance of family planning information, and husband's support with the choice of IUD contraception at the couples of reproductive age. From this research, the suggestion is that this research can be used as a reference for further research. The researcher hopes that further researchers will add the independent variables of the environment and the support of health workers.